The influence of soccer shoe design on player performance and injuries - Hennig, E. . (Research in Sports Medicine, 2011)
Although soccer is the most popular sport in the world, little research has been published in the field of soccer biomechanics, particularly on the importance of footwear for the game. The traction properties of soccer shoes on natural and artificial turf have been speculated to be responsible for acute and chronic injuries in soccer. This article reviewed the current knowledge on how soccer shoes influence the risk of injuries and how they may serve to improve player performance. Comfort is the highest priority that players want from their shoes, followed by traction and stability. Cleat design and arrangement are important shoe features that allow for fast accelerations and stops, rapid cuts, and turns. Soccer shoe design can influence shooting speed and, even more important for the game of soccer, kicking accuracy. To combine shoe characteristics for injury prevention and better performance will be a challenge for future research on optimizing soccer shoes.